Estrogens Determine Adherens Junction Organization and E-Cadherin Clustering in Breast Cancer Cells via Amphiregulin - Bischoff, Philip; Kornhuber, Marja; Dunst, Sebastian; Zell, Jakob; Fauler, Beatrix; Mielke, Thorsten; Taubenberger, Anna; Oelgeschlaeger, Michael; Schoenfelder, Gilbert; Guck, Jochen (iScience, 2020)
Estrogens play an important role in the development and progression of human cancers, particularly in breast cancer. Breast cancer progression depends on the malignant destabilization of adherens junctions (AJs) and disruption of tissue integrity. We found that estrogen receptor alpha (ERα) inhibition led to a striking spatial reorganization of AJs and microclustering of E-Cadherin (E-Cad) in the cell membrane of breast cancer cells. This resulted in increased stability of AJs and cell stiffness and a reduction of cell motility. These effects were actomyosin-dependent and reversible by estrogens. Detailed investigations showed that the ERα target gene and epidermal growth factor receptor (EGFR) ligand Amphiregulin (AREG) essentially regulates AJ reorganization and E-Cad microclustering. Our results not only describe a biological mechanism for the organization of AJs and the modulation of mechanical properties of cells but also provide a new perspective on how estrogens and anti-estrogens might influence the formation of breast tumors.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cancer; Cell Biology